Digu Puja: A ritual to revitalize the family unity among the Newars - Manandhar, Tina (Nepalese Culture, 2020)
Digu puja is a ritual of worshipping lineage god among the Newars of Kathmandu valley. With the brief discussion of the puja rituals this paper gives a detailed account of the family system in Nepal starting from ancient period. Following the developments in the field of education and politics how the joint family system was disintegrated and how the concept of nuclear family emerged in Nepal will also be discussed. And finally, how other festivals along with Digu Puja are helping to create a binding link amongst the separated family members will be analyzed.